Optimized peptide amount and activity for 90Y-labeled DOTATATE therapy - Kletting, Peter; Glatting, Gerhard (Journal of nuclear medicine, 2016)
In peptide receptor radionuclide therapy with 90Y-labeled DOTATATE, the kidney absorbed dose limits the maximum amount of total activity that can be safely administered in many patients. A higher tumor-to-kidney absorbed dose ratio might be achieved by optimizing the amount of injected peptide and activity, as recent studies have shown different degrees of receptor saturation for normal tissue and tumor. The aim of this work was to develop and implement a modeling method for treatment planning to determine the optimal combination of peptide amount and pertaining therapeutic activity for each patient. Methods: A whole-body physiologically based pharmacokinetic (PBPK) model was developed. General physiologic parameters were taken from the literature. Individual model parameters were fitted to a series (n = 12) of planar γ-camera and serum measurements (111In-DOTATATE) of patients with meningioma or neuroendocrine tumors (NETs). Using the PBPK model and the individually estimated parameters, we determined the tumor, liver, spleen, and red marrow biologically effective doses (BEDs) for a maximal kidney BED (20 Gy2.5) for different peptide amounts and activities. The optimal combination of peptide amount and activity for maximal tumor BED, considering the additional constraint of a red marrow BED less than 1 Gy15, was individually quantified. Results: The PBPK model describes the biokinetic data well considering the criteria of visual inspection, the coefficients of determination, the relative standard errors (<50%), and the correlation of the parameters (<0.8). All fitted parameters were in a physiologically reasonable range but varied considerably between patients, especially tumor perfusion (meningioma, 0.1-1 mL·g-1·min-1, and NETs, 0.02-1 mL·g-1·min-1) and receptor density (meningioma, 5-34 nmol·L-1, and NETs, 7-35 nmol·L-1). Using the proposed method, we identified the optimal amount and pertaining activity to be 76 ± 46 nmol (118 ± 71 μg) and 4.2 ± 1.8 GBq for meningioma and 87 ± 50 nmol (135 ± 78 μg) and 5.1 ± 2.8 GBq for NET patients. Conclusion: The presented work suggests that to achieve higher efficacy and safety for 90Y-DOATATE therapy, both the administered amount of peptide and the activity should be optimized in treatment planning using the proposed method. This approach could also be adapted for therapy with other peptides.
Gesehen am 08.04.2019
Im Titel ist "90" hochgestellt
Published online: December 17, 2015